الأوقاف الهبطية في ضوء تعقبات الشيخ الغماري - ربع البقرة أنمودجا - بالمسعود, عبد الجليل; بن عشورة, عبد الإله (University of Eloued-جامعة الوادي, 2022)
"تناولنا في هذه الدراسة: "" تعقبات الإمام عبد الله الغماري على وقوف الإمام أبي جمعة الهبطي ـ ربع البقرة-أنموذجا-""، التي أوردها الامام الغماري في كتابه ""منحة الرؤوف المعطي ببيان ضعف وقوف الهبطي"" وللإجابة على هذا الإشكال قمنا بتقسيم بحثنا إلى أربعة محاور، تناولنا في المحور الأول علم الوقف وما يحتويه وفي المحور الثاني والثالث ترجمة للإمامين أبي جمعة الهبطي والإمام عبد الله الغماري مع ذكر بعض من حياتهم أما في المحور الرابع فجعلناه للدراسة التطبيقية على تلك المواضع المنتقدة من ربع البقرة، ونهدف من خلالها إلى إظهار الجوانب اللغوية والنحوية والتفسيرية التي كان لها أثر في الوقوف الهبطية المبنية على اختيارات العلماء، -ثم ختمنا دراستنا بجملة من النتائج والتوصيات ومن أهمها: -أن وقوف الإمام الهبطي أغلبها مرضية وليس فيها من الخطأ ما ترفض لأجله -أن أغلب انتقادات الإمام الغماري كانت على صعيد التفسير والقراءات بحيث أنه متأثر بحفص وقالون. -نوصي كل من اهتم بهذه الوقوف (الهبطية) عليه أن يراعي من سبق الإمام الهبطي أمثال الإمام نافع -نوصي جميع الدارسين والباحثين في هذا الفن أن لا يميلوا بتعصب نحوا أحد العلماء. ""In this study, we dealt with: ""Imam Abdullah Al-Ghamari's repercussions on the standing of Imam Abu Juma'a Al-Habi - a quarter of the cow - as a model -"", which was mentioned by Imam Al-Ghamari in his book ""Minhat Al-Raouf Al-Maati with a statement about the weakness of Al-Habi's standing."" In order to answer this problem, we divided our research into four axes. In the first axis, we dealt with the science of the endowment and what it contains, and in the second and third axis, a translation of the two Imams Abi Juma'a Al-Habi and Imam Abdullah Al-Ghamari with mentioning some of their lives. And the interpretation that had an impact on the downward stance based on the choices of scholars, Then we concluded our study with a number of results and recommendations, the most important of which are: Most of the standing of Imam al-Habati is satisfactory, and there is nothing wrong with it that it is rejected for - Most of the criticisms of Imam Al-Ghamari were on the level of interpretation and readings, as he was influenced by Hafs and Qalon. We recommend that everyone who is interested in this (lower) standing should pay attention to the likes of Imam Nafi’ who preceded Imam Nafi’. We recommend to all scholars and researchers in this art not to be biased towards one of the scholars. "
مذكرة ماستر
Keywords: الأوقاف الهبطية، تعقيبات الإمام الغماري، ربع البقرة، الإمام الهبطي.; the landing endowments, the comments of Imam Al-Ghamari, the quarter of the cow, Imam Al-Hubti..